nteractional Metadiscourse in Applied Linguistics Master theses: A Corpus Based Comparative Study - Bouchemet, Tahar (Journal of Human Sciences, 2019)
The purpose of the present study is to examine the interactional metadiscourse features in the introduction and conclusion sections of the Master dissertations written by Algerian students at the University of Constantine 1. The analysis is based on a corpus of 20 Master dissertations introductions and conclusions from Applied Language Studies Discipline. This study seeks to show the distribution of interactional metadiscourse in students’ dissertations sections and the differences in the use of these features. The analysis of this study shows that the distribution of Interactional metadiscourse signals differs in the two sections. The findings of this study may have some pedagogical implications for teaching writing in academic disciplines and genres especially to EFL learners.